DAMPAK MEDIA PEMBELAJARAN BERBASIS DIGITAL TERHADAP LITERASI IPAS PADA SISWA KELAS IV SEKOLAH DASAR - Aay Aisyah; Agus Muharam; Atep Lesmana (STKIP Subang, 2026)
This study aimed to analyze the impact of digital-based learning media on the Science and Social Studies (IPAS) literacy of fourth-grade elementary school students. The research employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest–Posttest Design. The participants consisted of 23 fourth-grade students at SDN Kamurang 1, Karawang Regency, selected through a total sampling technique. Data were collected through IPAS literacy tests, observations, and documentation, and were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon Signed Rank Test, N-Gain analysis, and effect size. The results showed that the mean pretest score of 51.85 increased to 73.48 on the posttest. The Wilcoxon Signed Rank Test yielded a significance value of 0.000 (p < 0.05), indicating a significant effect of digital-based learning media on students' IPAS literacy. The N-Gain score of 0.46 was categorized as moderate, while the effect size of 0.876 indicated a very large effect. Therefore, digital-based learning media were proven to be effective in improving the IPAS literacy of elementary school students